Environmental benefits of blue ecosystem services and residents’ willingness to pay in Khulna city, Bangladesh - Md. Nazmul Haque; Mustafa Saroar; Md. Abdul Fattah; Syed Riad Morshed (Heliyon, 2022)
Nature-based solutions for urban problems gaining popularity globally. The well-functioning ecosystem could offer a nature-based solution to many urban problems including water, drainage and flooding problems. Therefore, conservation and restoration of urban blue ecosystem components such as pond scape are crucial. This research taking Khulna city of Bangladesh as a case has examined the low-income fringe community's willingness to pay (WTP) for conservation and restoration of pond scape/blue ecosystem service (BES) in their locality from where they benefit. The various types of ecosystem services enjoyed by the local community were identified. To assess the community's WTP for conservation and restoration of pond scape, the payment card approach of the Contingent Valuation Method (CVM) was used. Three environmental attributes were considered to assess the existing condition of the blue ecosystem services in the study area. Findings show that 54% of respondents are not satisfied with the existing conditions of the ecosystem services resulting from the pond scape. Respondent's WTP for eleven types of service facilities was calculated. Results show that only 65.20% are eager to pay an amount of 38 Tk to 138 Tk per month for different service facilities. It means about one-third of the community people want to be free riders. The influences of different attributes of the respondents on their WTP were also analyzed. Education, income, and house-ownership appear to have a positive significant influence on WTP for conservation and restoration of pond scape in the study area. In line with the findings if policy measures are taken without further delay it would help conserve the remaining pond scape.